CLRM-14. OPEN-LABEL, MULTINATIONAL, MULTICENTER, PHASE 3B/4 STUDY OF TRASTUZUMAB DERUXTECAN (T-DXD) IN PATIENTS WITH OR WITHOUT BASELINE BRAIN METASTASIS (BM) WITH PREVIOUSLY TREATED ADVANCED/METASTATIC HUMAN EPIDERMAL GROWTH FACTOR RECEPTOR 2–POSITIVE BREAST CANCER (HER2+ BC): DESTINY-BREAST12. (21st September 2021) - Lin, Nancy U; Ciruelos, Eva; Jerusalem, Guy; Müller, Volkmar; Niikura, Naoki; Viale, Giuseppe; Oscroft, Emma; Anand, Shawn; Walker, Graham; Harbeck, Nadia
Abstract: BACKGROUND: Despite treatment advances, up to 50% of patients with advanced HER2+ BC develop BM (Zimmer. Cancer Rep. 2020). Patients with HER2+ BC with BM have a worse prognosis than patients without BM. In DESTINY-Breast01, T-DXd demonstrated efficacy in the overall population and preliminary efficacy in a subgroup with stable BM, with a confirmed objective response rate (ORR) of 61.4% and an extracranial confirmed ORR by independent central review (ICR) of 58.3%, median progression-free survival (PFS) of 19.4 and 18.1 mo, and median duration of response (DOR) of 20.8 and 16.9 mo (Modi. Cancer Res. 2021; Jerusalem. Ann Oncol. 2020). Here we describe a trial evaluating T-DXd in patients with previously treated advanced/metastatic HER2+ BC ±BM. DESIGN: DESTINY-Breast12 (NCT04739761) is an open-label, multicenter, international (86 sites in the US, Europe, Australia, and Japan), phase 3b/4 study assessing T-DXd 5.4 mg/kg q3w efficacy and safety in patients with previously treated advanced/metastatic HER2+ BC ±BM that progressed with ≥1 prior anti-HER2–based regimen and received ≤2 lines of therapy in the metastatic setting (excluding patients with prior tucatinib). Patients (n=250/cohort) will be enrolled in cohort 1 (−BM at baseline) or 2 (+BM at baseline). BM must be untreated and not needing immediate local therapy or previously treated and stable or progressing. Primary endpoints are ORR (cohort 1) and PFS (cohort 2) (both by RECIST version 1.1 per ICR). Secondary endpoints are OS, DOR, time to progression, duration of subsequent therapy, PFS2, safety, and changes in symptoms, functioning, and QOL in both cohorts; incidence of new symptomatic CNS metastasis (CNSM) in cohort 1; and ORR and CNS ORR by RECIST 1.1 per ICR, CNS PFS and DOR, and time to new CNSM in cohort 2. This is an encore; the original presentation will be at The European Society for Medical Oncology 2021.